Phosphorylation-dependent WRN-RPA interaction promotes recovery of stalled forks at secondary DNA structure - Alessandro Noto; Pasquale Valenzisi; Flavia Di Feo; Federica Fratini; Tomasz Kulikowicz; Joshua A. Sommers; Benedetta Perdichizzi; Maurizio Semproni; Valentina Palermo; Marco Crescenzi; Robert M. Brosh Jr; Annapaola Franchitto; et al. (Nature Communications)
Abstract The WRN protein is vital for managing perturbed replication forks. Replication Protein A strongly enhances WRN helicase activity in specific in vitro assays. However, the in vivo significance of RPA binding to WRN has largely remained unexplored. We identify several conserved phosphorylation sites in the acidic domain of WRN targeted by Casein Kinase 2. These phosphorylation sites are crucial for WRN-RPA interaction. Using an unphosphorylable WRN mutant, which lacks the ability to bind RPA, we determine that the WRN-RPA complex plays a critical role in fork recovery after replication stress countering the persistence of G4 structures after fork stalling. However, the interaction between WRN and RPA is not necessary for the processing of replication forks when they collapse. The absence of WRN-RPA binding hampers fork recovery, causing single-strand DNA gaps, enlarged by MRE11, and triggering MUS81-dependent double-strand breaks, which require repair by RAD51 to prevent excessive DNA damage.